Spiritual Transformation of Former Drug Addicts Through Islamic Mindfulness at Islamic Boarding School - Suroyya, Naharin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine Islamic mindfulness-based healing techniques, analyze their roles, mechanisms of spiritual recovery, and the spiritual transformation of former drug addicts, as well as explore their contribution to a comprehensive rehabilitation model implemented at Pesantren Al Ghazali Kediri. This research employs a qualitative method with a case study design. Data collection techniques include observation, in depth interviews, and documentation involving students, mentors, and caregivers of the pesantren. Data analysis uses an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity is ensured through source triangulation, technique triangulation, member checking, and an audit trail. The findings indicate that Islamic mindfulness based healing techniques are implemented through the practices of muraqabah, tazkiyatun nafs, and muhasabah which effectively enhance self awareness, emotional regulation, and control over addictive impulses. The recovery mechanism operates through stages of awareness, self regulation, and the development of adaptive responses. In addition, spiritual transformation occurs, marked by changes in self identity, an increased sense of life meaning, and resilience against relapse. This approach contributes to a comprehensive rehabilitation model that integrates cognitive, emotional, behavioral, and spiritual aspects in a sustainable manner, thereby fostering enduring intrapersonal transformation among former drug addicts.